Exploring the elements of design - Evans, Poppy; Thomas, Mark (Delmar/Cengage Learning, 2013)
Offering a practical and visual introduction to the world of graphic design, this book provides readers with detailed coverage of design concepts, including color, imagery, creative thinking, and visual-problem solving, as well as an overview of the field of graphic design and related career options.